Taxation Policy and Compliance Burden on MSMEs: An In-depth Legal Study in Indonesia - Judijanto, Loso (International Journal of Business, Law, and Education, 2024)
Micro, Small, and Medium-Sized Enterprises (MSMEs) are shaped by tax laws, which have a major impact on their growth prospects, competitiveness, and conduct. MSMEs in Indonesia confront many obstacles when it comes to adhering to tax laws, such as intricate administrative procedures, expensive compliance fees, and restricted access to incentives. Using a normative analysis technique, this research undertakes a comprehensive legal study to assess taxation policies and compliance constraints on MSMEs in Indonesia. The results highlight the necessity of focused initiatives to improve taxpayer education, increase incentive accessibility, streamline tax laws, and provide compliance support. By tackling these issues, Indonesia can provide a tax climate that is more favorable and supportive of MSMEs, promoting entrepreneurship, economic growth, and sustainable development.